2014
DOI: 10.1111/hae.12470
|View full text |Cite
|
Sign up to set email alerts
|

Similar bleeding phenotype in young children with haemophilia A or B: a cohort study

Abstract: The bleeding phenotype has been suggested to differ between haemophilia A and B. More knowledge on the bleeding phenotype at initiation of treatment is important to optimize patient care. The aim of this study was to investigate the severity of the bleeding phenotype and the variation in bleeding in children with severe or moderate haemophilia A and B. Consecutive, previously untreated patients with severe or moderate haemophilia A and B (factor VIII or IX activity <0.01 or 0.01-0.05 IU mL(-1) respectively) bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 14 publications
5
31
0
1
Order By: Relevance
“…However, for separating haemophilic patients from healthy volunteers, peak seems to be a more sensitive parameter than ETP, as already described . No significant difference in ETP or peak was found between HA and HB patients with the same degree of disease severity, corroborating the finding that bleeding phenotype does not differ between HA and HB patients …”
Section: Discussionsupporting
confidence: 83%
“…However, for separating haemophilic patients from healthy volunteers, peak seems to be a more sensitive parameter than ETP, as already described . No significant difference in ETP or peak was found between HA and HB patients with the same degree of disease severity, corroborating the finding that bleeding phenotype does not differ between HA and HB patients …”
Section: Discussionsupporting
confidence: 83%
“…Another question being discussed is whether patients with haemophilia B have the same need for prophylaxis as patients with haemophilia A. It has recently been shown that there is no difference in the bleeding phenotype in young children with haemophilia A compared to those with haemophilia B (Clausen et al , ). Using the PedNet Registry, Clausen et al () found no difference in children between the bleeding phenotype of severe or moderate haemophilia A and B using parameters such as the age at diagnosis, the age at first bleed or first joint bleed, the time from first to second joint bleed or the age at first treatment.…”
Section: Prophylactic Treatment Is Superior To On‐demandmentioning
confidence: 99%
“…The participating centers are mainly in Europe with some centers in Canada and Israel. Among the important publications from this study were a report suggesting that one second generation recombinant FVIII concentrate was associated with a higher rate of inhibitors [18,43], and papers on the risk factors for inhibitor development in PUPs [44,45]. In terms of adverse events the RODIN study collects data only on inhibitor development.…”
Section: Specific Multicenter Schemes A) Rodinmentioning
confidence: 99%